DECODE-based STEM workshop in improving academic resilience and teaching competency of pre-service teachers - Rajasekaran, Rajasekaran; Sreedevi, P S; Chang, Chun-Yen (Eurasia Journal of Mathematics, Science and Technology Education, 2024)
This study examines DECODE model and academic resilience to improve pre-service teachers’ (PSTs) teaching abilities. Effective teaching in the changing context of education requires pedagogical skills and problem-solving. Teacher resilience is becoming more important to adapt and succeed in adversity. Development, inquiry, cooperation, observation, debate, and assessment make DECODE model a revolutionary teaching method. This study examines how DECODE adoption and academic resilience affect PSTs’ progress to influence teacher preparation and training. DECODE paradigm, instructional competence, and academic resilience are contextualized in this literature review. STEM-based workshop for 97 PSTs from various academic levels. Linked samples JAMOVI t-test examines academic resilience changes post-workshop. Both t-values and p-values (<0.05) show a statistically significant improvement in academic resilience. DECODE model improves participant scores for teaching competency statistically significantly. Teaching effectiveness and resilience are linked, emphasizing the necessity for thorough teacher preparation. Results show DECODE model and the training improve teaching skills and academic resilience.